Role of Trusting Beliefs in Predicting Online Purchase Intentions - Edi Komara (Journal of Economics and Business Aseanomics (JEBA), 2020)
Consumer behavior in every country, especially developing countries, must be different from consumer behavior in developed countries. This is a challenge faced by online shopping platforms to enter the Indonesian market by developing a new culture in terms of online shopping, as well as fostering trust in consumers in the products offered in order to attract consumer purchases. The success of a company in this case is e-commerce, namely the trust that is felt so that consumers have an interest in buying. Five marketplaces, namely Shopie, Bukalapak, Tokopedia, Lazada, and Blibi.com as providers of online product sales vendors from abroad must build trust that can be trusted for consumers, especially millennial consumers, in making transactions through online which causes consumer purchase interest, especially millennial consumers. Who are close to the development of the internet and receive new information in conducting online transactions.The design of this study uses an explanative analysis method by taking samples and questionnaires as the main tools, with the criteria of millennial consumer respondents, knowing products sold from abroad, and never product transactions from abroad. The data collected in this study were 110 respondents. By using the analysis technique of Structural Equation Modeling (SEM).The results showed that Uncertainty Avoidance had a negative and insignificant effect on Trusting Beliefs; Price Fairness had a positive and significant effect on Trusting Beliefs. Firm's Reputation has a positive and significant effect on Trusting Beliefs, and Trusting Beliefs has a positive and significant effect on Purchase Intention.